Maintenance management - Mann, Lawrence (Canada. : Lexington Books, 1976)
The author has had experience in many plants and has found that, although plant management is aware of the need for maintenance management, few programs are operating as they were anticipated to operate.This book is intended not only to assists maintenance management in implementing the more modern aspects of their jobs, but also to assist those managers in designing an up-to-date program if that is their desire.
Includes index.
Includes bibliographical references and index.
hza 26/07/2018
Loans
Keywords: Plant maintenance